Detection of Complement C1q B Chain Overexpression and Its Latent Molecular Mechanisms in Cervical Cancer Tissues Using Multiple Methods - Si-Tong Lin; Zi-Qian Liang; Xiao-Yu Chen; Xin-Qing Ye; Yu-Yan Pang; Jia-Yuan Luo; Jun-Hong Chen; Yi-Wu Dang; Gang Chen (International Journal of Genomics)
Aim. The aim of this study is to demonstrate the expression and clinicopathological significance of complement C1q B chain (C1QB) in cervical cancer. Methods. In total, 120 cervical cancer tissues, as well as 20 samples each of high-grade squamous intraepithelial lesions (HSILs), low-grade squamous intraepithelial lesions (LSILs), and benign cervical tissue, were collected to evaluate the expression of C1QB protein via immunohistochemical staining. We conducted an integrated analysis of C1QB mRNA expression in cervical cancer using public microarrays and RNA-seq data sets by calculating standard mean differences (SMDs). Simultaneously, we explored the relations of C1QB with clinicopathological parameters and the expression of P16, Ki-67, and P53. Results. The expression of C1QB protein was higher in cervical cancer samples than that in benign cervical tissue, LSIL, and HSIL samples (p<0.05). A combined SMD of 0.65 (95% CI: [0.52, 0.79], p<0.001) revealed upregulation of C1QB mRNA in cervical cancer. C1QB expression may also be related to the depth of infiltration, lymphovascular invasion, and perineural invasion in cervical cancer (p<0.05). We also found that C1QB protein expression was positively correlated with P16 and Ki-67 expression in cervical cancer (p<0.05). The gene set enrichment analysis showed that C1QB may participate in apoptosis and autophagy. A relationship was predicted between C1QB expression and drug sensitivity to cisplatin, paclitaxel, and docetaxel. Conclusion. We confirmed the overexpression of C1QB in cervical cancer at both mRNA and protein levels for the first time. C1QB may serve as an oncogene in the tumorigenesis of cervical cancer, but this possibility requires further study.